2020
DOI: 10.5267/j.msl.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of academicians recycling behaviour

Abstract: The main purpose of this study was to identify the determinants of recycling behaviour among academicians by utilizing the theory of planned behaviour (TPB). It also examined the mediating role of attitude in the relationship between environmental beliefs and recycling behaviour. An online survey was conducted among lecturers in a public university in Malaysia and 101 valid responses were received. Data was analysed using Partial Least Squares Structural Equation Modelling. Out of the six proposed hypotheses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Without the actions and support of employees towards sustaining the environment, there will be decreased environmental performance (Kim et al, 2019). Muniandy and Anuar (2020) argued that the lack of environmental sustainability engagement among university stakeholders, most especially academics, is hindering the efficient ‘greening’ of HEIs. Consequently, there is a disconnect between implementing environmental sustainability and the participation of academic employees of HEIs.…”
Section: Introductionmentioning
confidence: 99%
“…Without the actions and support of employees towards sustaining the environment, there will be decreased environmental performance (Kim et al, 2019). Muniandy and Anuar (2020) argued that the lack of environmental sustainability engagement among university stakeholders, most especially academics, is hindering the efficient ‘greening’ of HEIs. Consequently, there is a disconnect between implementing environmental sustainability and the participation of academic employees of HEIs.…”
Section: Introductionmentioning
confidence: 99%
“…Waste management is a pro-environmental behavior related to factors such as attitudes, norms, and behavioral control which are important determinants (Liao and Li, 2019). In the context of higher education, environmental education provides knowledge, influences attitudes towards waste management, and directs them to good and correct waste management intentions and behaviors (Liao and Li, 2019;Muniandy and Anuar, 2020). The theory of planned behavior (TPB) provides a theoretical framework in identifying factors that influence pro-environmental behavior such as, environmentally friendly purchases (Yadav and Pathak, 2016;Yazdanpanah and Forouzani, 2015) and travel behavior (Amaro and Duarte, 2015), and waste management (Heidari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have shown that manufacturing industries consume much energy and contribute immensely to environmental degradation (Fernando & Hor, 2017;Masri & Jaaron, 2017;Yong et al, 2020), they have also shown that HEIs consume a large number of resources, such as energy, water, and solid wastes, and exhume as much carbon emissions, causing negative impact to the environment (Abdul-Azeez & Ho, 2016;Tangwanichagapong et al, 2017). In response to the worsening degradation, HEIs have also taken responsibility in protecting the environment, engaged more fully in CSR, and incorporated environmental sustainability as one of their core values, with this decision receiving a full endorsement from the United Nations (Muniandy & Anuar, 2020).…”
Section: Introductionmentioning
confidence: 99%